Post-dural puncture headache with a previously unknown arachnoid cyst - Atilla Bilal Bezen, Elif Doğan Bakı, Özlem Çetin Akıcı (International Journal of Surgery and Medicine, 2019)
Postdural puncture headache (PDPH) is a common complication after neuroaxial anesthesia or analgesia procedures. Several factors are thought to contribute to this adverse situation for both patients and practitioners. This headache may also be known as positional headache because of the feature of usually worsening when standing and relief being obtained in a recumbent position. Numerous options have been described for treatment and prevention. There are reports in literature of rare cases of PDPH with arachnoid cyst. The case is here reported of a patient with PDPH after spinal anesthesia with a previously unknown arachnoid cyst, and the treatment and prevention are discussed.